Effect of dietary ion supplementation on the survival and growth of Penaeus vannamei during the pre-nursery stage in well water - Ordoñez-Iglesias, Juan; Zambrano-Ostaiza, Agustin; Méndez-Martínez, Yuniel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Aquaculture has become an essential activity to ensure global food security, with white shrimp (Penaeus vannamei) standing out as one of the most important species due to its high demand and adaptability to diverse environments. This study aimed to evaluate the effect of dietary ion supplementation on the survival, growth and feed efficiency of P. vannamei during the pre-nursery stage using well water. The experiment included a control treatment (T0) with seawater (34 ppt) and no added ions, and three treatments using well water and ion-supplemented diets: T1 (0.1 mg Ca²⁺, 1.2 mg Mg²⁺, 0.4 mg K⁺), T2 (0.2 mg Ca²⁺, 2.2 mg Mg²⁺, 0.8 mg K⁺), and T3 (0.4 mg Ca²⁺, 4.2 mg Mg²⁺, 1.4 mg K⁺). Each treatment consisted of three replicates, with 50 post-larvae per tank, over a 28-day period. Statistically significant differences (p<0.05) were observed in survival, growth and feed conversion ratio (FCR). The highest growth (1.03 %) was recorded in T0, followed by T2 (0.91 %) and T3 (0.83 %), while T1 showed the lowest growth (0.68 %) and the best FCR (1.027). Treatment T3 showed a favorable balance between growth and survival (94.5 %) with a competitive FCR (1.091). It is concluded that dietary ion supplementation improves the zootechnical performance of P. vannamei cultured in well water, and that appropriate adjustment of Ca²⁺, Mg²⁺, and K⁺ concentrations in feed can optimize both survival and feed efficiency under low-salinity conditions.